TRANSFORMING TRADITIONAL CUISINE INTO TECHNOPRENEURIAL INNOVATION: NASI TUTUG ONCOM (NTO) AS A GASTRONOMIC TOURISM ATTRACTION - Rahmat, Silvia Wijaya; Pramudya, Wisnu; Ramadhan, Danny Rizky; Annajam, Getar Jagat Raya Rahmatul; Millah, Riza Saepul (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study examines the potential of nasi tutug oncom (NTO), a traditional Sundanese dish from Tasikmalaya, as a culturally rich, digitally marketable gastronomic tourism product. Although Indonesian culinary heritage has gained attention in tourism development, regional dishes like NTO are understudied in both research and policy. The study aims to (1) analyze the attractiveness of NTO as a tourism product, (2) evaluate existing promotional efforts and challenges, and (3) propose technopreneurial strategies to enhance its digital sustainability and marketability. A qualitative approach was employed through semi-structured interviews and participant observation with ten key stakeholders, including tourism officials, gastronomy experts, NTO producers, entrepreneurs, and travel agent. Using the "3S" framework: Something to See, Something to Do, and Something to Buy". Findings reveal that NTO offers a holistic gastronomic experience encompassing cultural observation, active participation, and economic contribution. However, current promotions are fragmented, with a limited digital presence and coordination. Technopreneurship emerges as a viable approach to repositioning NTO through digital storytelling, visual branding, and e-commerce. This study contributes to the discourse on gastronomic tourism by emphasizing regional culinary heritage and the importance of stakeholder collaboration and digital innovation in sustaining local gastronomy.Keyword: culinary heritage; digital promotion; gastronomic tourism; nasi tutug oncom (NTO); technopreneurshipAbstrak: Penelitian ini mengkaji potensi Nasi Tutug Oncom (NTO), sebuah makanan tradisional khas Sunda yang berasal dari Tasikmalaya, sebagai produk pariwisata gastronomi yang kaya budaya dan dapat dipasarkan secara digital. Meskipun warisan kuliner Indonesia telah mendapat perhatian dalam pengembangan pariwisata, namun makanan tradisional seperti NTO belum banyak dikaji baik dalam penelitian maupun kebijakan. Penelitian ini bertujuan untuk (1) menganalisis daya tarik NTO sebagai produk pariwisata, (2) mengevaluasi upaya promosi yang dilakukan sejauh ini beserta tantangannya, dan (3) menawarkan strategi technopreneurial untuk meningkatkan keberlanjutan digital dan daya pasarnya. Pendekatan kualitatif dipilih dengan memanfaatkan observasi partisipatif dan wawancara semi-terstruktur terhadap sepuluh pemangku kepentingan, di antaranya adalah dinas pariwisata, ahli gastronomi, produsen dan wirausahawan NTO, serta agen perjalanan. Penelitian ini menggunakan kerangka teori 3S: Something to See, Something to Do, and Something to Buy. Hasil penelitian menunjukkan bahwa NTO menawarkan pengalaman gastronomi secara menyeluruh yang mencakup pembelajaran budaya, partisipasi aktif, dan kontribusi ekonomi. Meskipun demikian, saat ini promosinya masih terfragmentasi, minim koordinasi, dan belum digital. Technopreneurship muncul sebagai strategi untuk memposisikan kembali NTO melalui storytelling digital, branding visual, dan e-commerce. Penelitian ini berkontribusi pada diskursus tentang pariwisata gastronomi dengan menekankan warisan kuliner lokal, pentingnya kolaborasi pemangku kepentingan, dan inovasi digital untuk mempertahankan gastronomi lokal.Kata kunci: warisan kuliner; promosi digital; pariwisata gastronomi; nasi tutug oncom (NTO); technopreneurship.